Accelerating The Global Competitiveness Of Nigerian Economy: The Role Of Polytechnic Education - Agu, Agu Godswill; Merenini, Godwin O.; Aja, Ebeke Egele (Advances in Social Sciences Research Journal, 2017)
The Global Competitiveness of Nigerian Economy has been ranked poor by the World Economic Forum (WEF) since the past ten years. The country has maintained a three-digit position for about a decade, averaging 114 out of 139 countries and 3.57 on a 7-point scale since the past nine years. Although poor infrastructure, corruption, and access to finance have been identified as the three most problematic factors to business, productivity and global competitiveness of the country, the inability of Nigeria to fully tap from the potentials of polytechnic education which is practical and productive oriented has contributed in worsening the country’s competitive ranking globally. This study x-rayed Nigeria’s ranking in the World Economic Forum’s Global Competitiveness Index from 2007 to 2015 and adopted the Porter’s Diamond Model in explaining the role of polytechnic education in enhancing Nigeria’s global competitiveness. Evidence from the WEF 2015/2016 report reveals that Nigeria remains one of the poorly ranked economies in terms of global competitiveness and productivity. The paper provides an insight into the untapped potentials of polytechnic education in Nigeria and how the country can leverage it to overcome economic recession and accelerate its global competitiveness and productivity.